Sudan's transition to war and the limits of the UN's good offices - Volker Perthes (Stiftung Wissenschaft und Politik (SWP), 2024)
The United Nations Integrated Transition Assistance Mission in Sudan (UNITAMS) was established at the request of Sudan's government to assist the country's political "transition" towards domestic peace and democratic governance. Rather then being able to see its mandate through, the Mission witnessed a transition to the ongoing war between the country's two military formations. UNITAMS' good-offices function came into play in all three phases of the Mission's lifespan - under the civilian-military partnership, under the military government, and in the first weeks of the war. Facilitation efforts became particularly relevant following the October 2021 military coup and after the conclusion of a Framework Political Agreement by the military and their civilian counterparts in December 2022. UNITAMS worked with a broad spectrum of civilian, "para-civilian" and military Sudanese stakeholders and with various regional and international partners. The establishment of the Tripartite Mechanism in cooperation with the African Union and the Inter-Governmental Authority on Development (IGAD) lent additional legitimacy to the efforts of all three organisations - and was at the same time a valuable learning exercise. One of the main lesson for international actors is not to underestimate the strength of actors who fear losing out in a transition process that the international community seeks to support. The UNITAMS experience demonstrates that even a small political mission can play an effective good-offices role, but it also shows the limits of this function - especially where military actors are set for war.
Keywords: 320; United Nations Integrated Transition Assistance Mission in Sudan; UNITAMS; Framework Political Agreement; Inter-Governmental Authority on Development; IGAD; Special Representative of the Secretary General for Sudan; SRSG; Sudanese Armed Forces; SAF; Rapid Support Forces; RSF; Comprehensive Peace Agreement; Juba Agreement for Peace in Sudan; JPA; Permanent Ceasefire Committee; PCC; Omar al-Bashir; Abd al-Fattah al-Burhan; Muhammad Hamdan Daglo; Hemedti; Abdallah Hamdok; Mini Minawi; Jibril Ibrahim; Malik Agar; Musa Hilal; Forces for Freedom and Change; FFC; Sudan People's Liberation Movement; SPLM; Justice and Equality Movement; JEM; Coalition of Civic Democratic Forces; Armed Struggle Movements; ASMs